Efforts On Increasing Creativity Through Finger Painting Activities In Early Education - Ade Amaliyah; Masganti Sit; Muhammad Basri (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2022)
Efforts on increasing creativity through finger painting activities in early education: developing children's creativity at a young age is necessary because creative children have an easier time solving their challenges. the development of children's creativity is suboptimal based on observations indicating that the teacher is less involved in the learning process and that the facilities available are restricted. this study aimed to determine children's creativity through finger painting activities. this research used 2 cycles of class action research (car) with 16 children as subjects. the data revealed pre-cycle and cycle 2 outcomes. in the pre-cycle, only 4 out of 6teen children had ideal development. in the first cycle, only 7 out of 6teen and thirteen out of 6teen children had an optimal effect in the second cycle. activities involving finger painting are beneficial for encouraging children's creativity. through finger painting, children's creativity can develop their adaptability, fluency, originality, and elaboration. the best developmental outcomes can be achieved if this exercise is performed regularly and under the supervision of professionals.